African farmer-led irrigation development: re-framing agricultural policy and investment?. Issue 1 (2nd January 2017) - Woodhouse, Philip; Veldwisch, Gert Jan; Venot, Jean-Philippe; Brockington, Dan; Komakech, Hans; Manjichi, Ângela
Abstract : The past decade has witnessed an intensifying focus on the development of irrigation in sub-Saharan Africa. It follows a 20-year hiatus in the wake of disappointing irrigation performance during the 1970s and 1980s. Persistent low productivity in African agriculture and vulnerability of African food supplies to increasing instability in international commodity markets are driving pan-African agricultural investment initiatives, such as the Comprehensive Africa Agricultural Development Programme (CAADP), that identify as a priority the improvement in reliability of water control for agriculture. The paper argues that, for such initiatives to be effective, there needs to be a re-appraisal of current dynamics of irrigation development in sub-Saharan Africa, particularly with respect to the role of small-scale producers' initiatives in expanding irrigation. The paper reviews the principal forms such initiatives take and argues that official narratives and statistics on African irrigation often underestimate the extent of such activities. The paper identifies five key characteristics which, it argues, contradict widely held assumptions that inform irrigation policy in Africa. The paper concludes by offering a definition of 'farmer-led irrigation' that embraces a range of interaction between producers and commercial, government and non-government agencies, and identifies priority areas for research on the growth potential and impact of such interactions and strategies for their future development.